2018
DOI: 10.1007/s00784-017-2328-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dental treatment on oral health-related quality of life in adolescents

Abstract: Providing dental treatment has beneficial effects on the quality of life of adolescents, especially for oral symptoms and emotional well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
3
12
1
3
Order By: Relevance
“…14,20 The comparison of results of overall and domain scores of the CPQ 11-14 instrument at baseline and 3-year follow up demonstrated that study participants had an improvement in their OHRQoL over time. This reduction in the prevalence of impacts across the whole sample over time was also observed in in the few longitudinal studies already published, 16,18,19 using the same OHRQoL instrument. One hypothesis, based on the theoretical underpinnings of OHRQoL 1,14,25,29 is that the improvement may have occurred due to changes in the self-perception of body image, as well as changes in psychological, socioeconomic and environmental factors of adolescents at age 12 and 15, which may have directly influenced on their OHRQoL.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…14,20 The comparison of results of overall and domain scores of the CPQ 11-14 instrument at baseline and 3-year follow up demonstrated that study participants had an improvement in their OHRQoL over time. This reduction in the prevalence of impacts across the whole sample over time was also observed in in the few longitudinal studies already published, 16,18,19 using the same OHRQoL instrument. One hypothesis, based on the theoretical underpinnings of OHRQoL 1,14,25,29 is that the improvement may have occurred due to changes in the self-perception of body image, as well as changes in psychological, socioeconomic and environmental factors of adolescents at age 12 and 15, which may have directly influenced on their OHRQoL.…”
Section: Discussionsupporting
confidence: 75%
“…This fact could be expected a priori due to several factors, including the absence of clinical changes and no pain and discomfort related to dental caries over time. 2,18 On the other hand, worsening CPQ 11-14 scores over time were observed among the DMFT increment group. In this group, the Functional Limitation (FL) domain of CPQ 11-14 presented worsening over time, with a statistically significant difference between Table 5.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Dental pain and using a mouth rinse were not significantly correlated with the DMFT scores of mother and child, but these two variables were related to the DT scores. Brondani et al (2018) reported that dental treatment resulted in a significant improvement in the Oral Healthrelated Quality of Life (OHRQoL) of the evaluated adolescents. Children's dental care can improve their OHRQoL, and, as such, children's teeth should not be left untreated.…”
Section: Discussionmentioning
confidence: 99%
“…This was evident in recent systematic reviews, which concluded that children with a high dental caries rate have poor school attendance and poor academic achievement . In a longitudinal study, when treatments for decayed teeth were provided, significant improvement on OHRQoL was demonstrated among South Brazilian adolescents …”
Section: Introductionmentioning
confidence: 91%